Internalizing symptoms, medication adherence, and perceived social support in individuals with inflammatory bowel disease - Bascom, Elise, author; Borrayo, Evelinn, advisor; Rickard, Kathryn M., committee member; Weir, Tiffany, committee member (Colorado State University. Libraries, 2017)
The present study examines perceived social support for individuals with inflammatory bowel disease (IBD). Patients were recruited for this study from online forums consisting of Facebook support groups, Twitter followers, and email. This study investigated sociodemographic and disease-related predictors of disease severity for individuals with IBD, as well as whether or not perceived social support moderates the relationship between disease severity, internalizing symptoms, quality of life, and medication adherence. A sample size of 155 individuals self-reporting with inflammatory bowel disease (ulcerative colitis or Crohn's disease) completed questionnaires related to disease severity, disease type, disease duration, quality of life, depression, anxiety, stress, perceived social support, and medication adherence. The study findings suggest that anxiety and stress are potential predictors of scores on disease severity for this population. Results also suggests that perceived social support is likely to have (or had in this sample) a significant, moderating relationship between disease severity and anxiety, disease severity and stress, and disease severity and the full depression, anxiety and stress scale (DASS). Anxiety was also found to moderate the relationship between disease severity and adjusted quality of life (QoL) scale. Perceived social support did not moderate the relationship between disease severity and the abbreviated medication adherence rating scale (MARS) generated by principle component analysis. It is important to note that future research should include a more randomized, representative sample, allowing for more conclusive findings. Understanding the psychological impact associated with this disease provides continued evidence for the need support individuals coping with IBD.
Keywords: ostomy surgery; ulcerative colitis; inflammatory bowel disease; chronic illness; social support; Crohn's disease